IMPLEMENTASI ETIKA DAKWAH RASULULLAH SAW MELALUI MEDIA SOSIAL PADA MASA PANDEMI COVID-19 - Uswatun Hasanah (Ath Thariq Jurnal Dakwah dan Komunikasi, 2021)
The dakwah is one of the portrait of Islam, so the important thing to note in presenting the wah is an ethical matter, ethics being one of the keys to the dakwah success. The study concludes that some of the dakwah ethics ada 'i is to take note of neither word nor deed, and two do not tolerate agarna, do not berate others, do not discriminate, therefore the ethic of the dakwah is looked upon as the important thing to notice, rather the traditions of the people who not only pay attention to what is spoken but also who speaks. The dakwah should not be provocative, propaganda and coercion, nor is it lawful for ada 'i to charge a price in the dakwah, ada 'i is required to be fair and open to preaching with adequate depth of knowledge and experience.